2017
DOI: 10.5539/gjhs.v9n12p32
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Distribution of Comprehensive HIV/AIDS Knowledge in Ghana

Abstract: Globally, nearly 37 million people are living with HIV with about 70 percent of these living in Sub-Saharan Africa (SSA). Stigma and discrimination remain one of the major barriers to preventing new infections in the country. However, misconceptions about HIV/AIDS have been indicated as one of the key drivers of the disease. Efforts to prevent new infections have not been entirely successful. Therefore, this study aims to examine the trends and distribution in comprehensive knowledge of HIV and AIDS and determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
31
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 9 publications
23
31
2
Order By: Relevance
“…Similarly, women being in the highest wealth index had a good comprehensive knowledge of HIV/AIDS as compared to the poorest women. This result is in agreement with the study done in Nigeria and Republic of Congo [20], in Ghana [19], in three east African countries [17]. This is due to the reason that having good socioeconomic status improves media exposure or educational achievement which increases the likelihood of knowledge about HIV/AIDS [28].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, women being in the highest wealth index had a good comprehensive knowledge of HIV/AIDS as compared to the poorest women. This result is in agreement with the study done in Nigeria and Republic of Congo [20], in Ghana [19], in three east African countries [17]. This is due to the reason that having good socioeconomic status improves media exposure or educational achievement which increases the likelihood of knowledge about HIV/AIDS [28].…”
Section: Discussionsupporting
confidence: 91%
“…Some studies also showed that lower educational level [18], poor wealth index [17,19], and rural residence [20] and do not use contraceptives [21] were factors that decline comprehensive knowledge of HIV/AIDS among women of reproductive age. Having accurate HIV/AIDS knowledge about transmission and prevention is very important for avoiding HIV infection and ending the stigma and discrimination of infected and affected persons.…”
Section: Introductionmentioning
confidence: 99%
“…This is a worrisome nding as it suggests that some AGYW in Malawi are still lacking basic knowledge of HIV transmission as well as prevention methods. This result is consistent with the ndings of a study done in Ghana [15]. The present study has revealed that age, education, wealth index, frequency of listening to radio and work status were signi cantly associated with overall HIV/AIDS knowledge.…”
Section: Discussionsupporting
confidence: 93%
“…AGYW who had attained primary education and those who had secondary or higher education were more likely to have high overall knowledge of HIV/AIDS compared to those who had no education. This nding is consistent with the studies conducted in Kenya and Ghana [11,15]. There are various potential explanations for the positive correlation between education and overall HIV/AIDS knowledge.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation